2004
DOI: 10.1016/j.jtcvs.2004.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Reoperative laparoscopic fundoplication for the treatment of failed fundoplication

Abstract: Laparoscopic reoperation for failed fundoplication is feasible and can achieve resolution of symptoms for a significant percentage of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 36 publications
0
23
0
2
Order By: Relevance
“…5,[16][17][18][19][20][21][22]26,27,30,31,[45][46][47][48][49] The aggregate of published evidence suggests that revision laparoscopic fundoplication and hiatal herniorraphy is effective, but technically challenging; thus, these revisional procedures should probably be performed in specialty centers. More important, however, are lessons learned in minimizing failure after primary operation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,[16][17][18][19][20][21][22]26,27,30,31,[45][46][47][48][49] The aggregate of published evidence suggests that revision laparoscopic fundoplication and hiatal herniorraphy is effective, but technically challenging; thus, these revisional procedures should probably be performed in specialty centers. More important, however, are lessons learned in minimizing failure after primary operation.…”
Section: Resultsmentioning
confidence: 99%
“…5,[16][17][18][19][20][21][22][23] Others have noted issues with the hiatal disruption during laparoscopic revision fundoplication. 8,16,18,19,22,[24][25][26][27][28][29][30][31][32][33][34] Herniation of the wrap, whether due to short esophagus or inadequate repair of the hiatus, is a primary mechanism of failure after minimally invasive fundoplication. We feel that this is almost always secondary to an inadequate repair of the esophageal hiatus or insufficient esophageal mobilization, as opposed to a shortened esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…This includes procedures such as a Collis-Nissen for short esophagus, revision of failed fundoplications (laparoscopic or open), and repair of giant or recurrent hiatal hernias. Reports by Hunter, Anvari, Rosemurgy [10] and others [3,9] have demonstrated that these procedures can be undertaken safely with success rates of up to 95%. There also are a few small series in the pediatric population, including those by Tan and Wulkan [13] and Espisito et al [2], that show favorable results, as compared with open redo fundoplication.…”
Section: Discussionmentioning
confidence: 99%
“…The application of the inclusion and exclusion criteria using information available in the published abstracts left 35 articles for a full review. From this pool, the final 17 articles were selected [9,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. An additional review of the references in these final 17 articles yielded no additional publications for inclusion in the analysis.…”
Section: Search Yieldmentioning
confidence: 99%